Recent Developments Towards Synthesis of (Het)arylbenzimidazoles - Mamedov, Vakhid A.; Zhukova, Nataliya A. (Synthesis, 2021)
Benzimidazole is an important heterocycle that is widely researched and utilized by the pharmaceutical industry and is one of the five most commonly used five-membered aromatic heterocyclic compounds approved by the US Food and Drug Administration. In view of their wide-ranging bioactivities, systems containing benzimidazole as one of the moieties occupy a special place among other benzimidazole derivatives. Since 2010, many improved synthetic strategies have been developed for the construction of hetaryl- and arylbenzimidazole molecular scaffolds under environmentally benign conditions. This review emphasizes the recent trends and modifications frequently used in the synthesis of derivatives of benzimidazole such as the Phillips–Ladenburg and Weidenhagen reactions, as well as entirely new methods of synthesis, involving oxidative cyclization, cross-coupling, ring distortion strategy, and rearrangements carried out under environmentally benign conditions.1 Introduction2 From 1,2-Diaminobenzenes with Various One-Carbon Unit Suppliers2.1 Phillips–Ladenburg Reaction2.1.1 With (Het)arenecarboxylic Acids2.2.2 With (Het)arenecarboxylic Acid Derivatives2.2 Weidenhagen Reaction2.2.1 With (Het)arenecarbaldehydes or (Het)aryl Methyl Ketones2.2.2 With Primary Alcohols2.2.3 With Primary Alkylamines2.2.4 With 2-Methylazaarenes2.2.5 With Other One-Carbon Fragment Suppliers3 From 2-Haloacetanilides and Amines4 From Amidines5 From Tetrahydroquinazolines6 Mamedov Rearrangement7 Conclusions and Outlook
Keywords: benzimidazole; Phillips–Ladenburg reaction; Weidenhagen reaction; oxidative cyclization; C–N bond formation; ring distortion strategy; Mamedov rearrangement